Narrativa e ética: a formação humana na perspectiva de Paul Ricoeur - Bregalda, Regiano (2017)
The research to be presented resumes the work from Paul Ricoeur's, the Oneself as another, two nuclear concepts: hermeneutics of self and ethical aim. The problem is to investigate the extent to which such concepts contribute to a broad notion of human formation, capable of understanding the subject in its entirety and, therefore, what challenges point to educational processes. The hypothesis rests on the understanding that, in the connection between the hermeneutics of self, anchored in the idea of narrative, and the ethical aim, there is an idea of human formation that helps the subjects to read the world, guide their action, to give meaning to existence and, above all, to become connoisseurs of oneself. This is possible to be found in the aforementioned work of Ricoeur because in the act of narrating the subject meets the conditions of narrating, understanding himself in the narrated, attributing meaning to his existence, becoming conscious and responsible for oneself, as well as by what happens to it. The methodology that guides the research is of bibliographical character and is guided by an analytical-reconstructive and hermeneutic procedure of the work the Oneself as another and of commentators about the author and the theme. In the development of the dissertation, we return to the hermeneutic perspective of the self, which for Ricoeur constitutes narrative identity and allows the subject to signify his life in the mirror of words. After this step, the ricoeurian ethical perspective, deployed in the summary of the good life with and for the other in fair institutions and its close relation with the narrative, is deepened. It is concluded, finally, that the thinking of ricoeurian contributes in a decisive way to think human formation and educational processes, since postulate the idea of a capable subject, capacity that allows him to signify his existence, morally imputing his actions, as a being of relationships and interrelationships and of reading the world.